2004
DOI: 10.1021/ie040077m
|View full text |Cite
|
Sign up to set email alerts
|

Esterification Kinetics of Glycerol with Fatty Acids in the Presence of Zinc Carboxylates:  Preparation of Modified Acylglycerol Emulsifiers

Abstract: The main goal of this study is the elaboration of a one-step synthesis of acylglycerol emulsifiers with modified hydrophobic properties. The esterification kinetics of glycerol with four individual fatty acids (C12:0, C14:0, C16:0, and C18:0), in the presence of zinc carboxylates (ZnC) of these acids, was investigated. The influence of the ZnC concentration and temperature on the reaction progress was studied. It was found that, under the applied conditions, the process is, with respect to glycerol esterificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 25 publications
2
46
0
3
Order By: Relevance
“…Investigations on the effectiveness of acylglycerol emulsifiers, modified with sodium and potassium soaps, showed the possibility of using such emulsifiers for the stabilization of O/W emulsions [20]. As presented elsewhere [21,22] the modification of the hydrophobic properties of acylglycerol emulsifiers may be realized by means of the controlled esterification of glycerol with fatty acids in the presence of zinc or magnesium soaps. In contrast to the use of alkali soaps, the synthesized products are very effective in the stabilization of W/O-type emulsions.…”
Section: Introductionmentioning
confidence: 93%
“…Investigations on the effectiveness of acylglycerol emulsifiers, modified with sodium and potassium soaps, showed the possibility of using such emulsifiers for the stabilization of O/W emulsions [20]. As presented elsewhere [21,22] the modification of the hydrophobic properties of acylglycerol emulsifiers may be realized by means of the controlled esterification of glycerol with fatty acids in the presence of zinc or magnesium soaps. In contrast to the use of alkali soaps, the synthesized products are very effective in the stabilization of W/O-type emulsions.…”
Section: Introductionmentioning
confidence: 93%
“…3, 4, 5, 6). Literature reports that the HOAc:glycerol molar ratio is a key factor in these reactions [28,29]. However, data is scarce regarding glycerol esterification reactions catalysed by Lewis acids [30].…”
Section: Effects Of the Glycerol:hoac Molar Ratiomentioning
confidence: 99%
“…Macierzanka and Szelag [17] studied the esterification of glycerol in the presence of zinc carboxylates and found that this catalyst significantly influenced monoglyceride (MAG) conversion and its presence increased the glycerol-fatty acid interfacial area (increase of microemulsions formation). Di Serio and co-workers [18] described esterification reactions employing layered metal carboxylates or layered metal soaps (zinc acetate and stearate).…”
Section: Introductionmentioning
confidence: 99%